PROBLEMATIKA PENEGAKAN HUKUM LINGKUNGAN DALAM PENGELOLAAN FOOD WASTE PROGRAM MAKAN BERGIZI GRATIS (MBG) - Bhakti, Rainada Della Indira; Wahyudi (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2026)
The Free Nutritious Meals Program (MBG) is one of the government's strategic policies aimed at improving the nutritional status and quality of Indonesia's human resources, especially for school-age children. However, the implementation of this program on a national scale also has an environmental impact in the form of increased food waste, which has the potential to cause pollution if not managed properly. This study aims to examine the problems of environmental law enforcement in food waste management in the MBG Program. The method used is normative legal research with a legislative and conceptual approach, through analysis of legislation and environmental law principles. The results of the study show that food waste management in the MBG Program is not yet supported by clear and comprehensive technical regulations, and environmental law enforcement has not been optimal due to weak regulations, unclear division of authority, and low awareness and capacity of program implementers. In addition, the application of the principles of sustainable development, precautionary principle, and polluter pays principle has not been fully implemented in the program. Therefore, it is necessary to strengthen regulations, improve inter-agency coordination, and increase the capacity of implementers to ensure sustainable food waste management. KEYWORDS: Free Nutritious Meal Program, Food Waste, Environmental Law, Law Enforcement